1997
DOI: 10.1073/pnas.94.16.8697
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anti-anti-idiotypic antibodies that bind antigen and an anti-idiotype

Abstract: Two mouse monoclonal anti-anti-idiotopic antibodies (anti-anti-Id, Ab3), AF14 and AF52, were prepared by immunizing BALB͞c mice with rabbit polyclonal antiidiotypic antibodies (anti-Id, Ab2) raised against antibody D1.3 (Ab1) specific for the antigen hen egg lysozyme. AF14 and AF52 react with an ''internal image'' monoclonal mouse anti-Id antibody E5.2 (Ab2), previously raised against D1.3, with affinity constants (1.0 ؋ 10 9 M ؊1 and 2.4 ؋ 10 7 M ؊1 , respectively) usually observed in secondary responses agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the GAT (Glu 60 Ala 30 Tyr 10 ) model similar observations are noticed: ab1 and idiotype/antigen positive ab3 antibodies also display restrictive variation, and moreover, are encoded by the same V H genes (4). Similar observations were made with ab1 and ab3 mAbs against the branched synthetic polypeptide antigen poly-L-(Tyr,Glu)-poly-D,L-(Ala)-poly-L-(lys), designated (T,G)-A-L and egg lysozyme (6,18). Their models, however, are presumably based on an internal image type of the anti-idiotypic antibody, whereas ab2 mAb A321 is unequivocally of a noninternal image character (11).…”
Section: Resultssupporting
confidence: 75%
“…In the GAT (Glu 60 Ala 30 Tyr 10 ) model similar observations are noticed: ab1 and idiotype/antigen positive ab3 antibodies also display restrictive variation, and moreover, are encoded by the same V H genes (4). Similar observations were made with ab1 and ab3 mAbs against the branched synthetic polypeptide antigen poly-L-(Tyr,Glu)-poly-D,L-(Ala)-poly-L-(lys), designated (T,G)-A-L and egg lysozyme (6,18). Their models, however, are presumably based on an internal image type of the anti-idiotypic antibody, whereas ab2 mAb A321 is unequivocally of a noninternal image character (11).…”
Section: Resultssupporting
confidence: 75%
“…However, the idiopeptide of the antibody loaded onto the MHC class I, if similar to the antigen‐derived peptide, will generate T‐cell memory by keeping CD8 + cells at elevated frequencies with cycles of proliferation. Recently, it has been shown that CDR3 regions of anti antibody have a stretch of amino acids which are similar to the antigen 27,28 . It may be noted here that CD8 + T‐cell and B‐cell populations will exhibit an inverse relationship similar to a predator–prey relationship found in an ecosystem.…”
Section: Connectivity Between B‐cell Memory and T‐cell Memorymentioning
confidence: 66%
“…We have previously described idiotypic mimicry of MAb E8 in antianti-idiotypic Abs [Johnson and Moore, 2002]: it was interesting that, in the catalytic mimics, while there were obvious similarities in function (ester hydrolysis), there appeared to be significant differences in the active site structures, as deduced from their kinetic behavior and reaction with different substrates and inhibitors. The crystallographic structures of a number of antigen-anti-Id combinations have been solved; it is noteworthy that in no cases were the anti-idiotypic antibodies internal images replicas of the antigenic sites [e.g., Fields et al, 1995;Goldbaum et al, 1997]. Instead, considerable structural variation was found, in some cases with little or no sequence identity.…”
Section: Discussionmentioning
confidence: 99%